2020
DOI: 10.3389/fpsyg.2020.552355
|View full text |Cite
|
Sign up to set email alerts
|

When Grades Are High but Self-Efficacy Is Low: Unpacking the Confidence Gap Between Girls and Boys in Mathematics

Abstract: Girls have much lower mathematics self-efficacy than boys, a likely contributor to the under-representation of women in STEM. To help explain this gender confidence gap, we examined predictors of mathematics self-efficacy in a sample of 1,007 9th graders aged 13–18 years (54.2% girls). Participants completed a standardized math test, after which they rated three indices of mastery: an affective component (state self-esteem), a meta-cognitive component (self-enhancement), and their prior math grade. Despite hav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…Though expectancy has been identified as a strong predictor of academic success in previous studies (see Wigfield & Eccles, 2020), it depends more on individuals’ confidence in their intellectual abilities and their experiences with the activities (Eccles, 2005). Due to cognitive immaturity, children are often overly optimistic about their competencies in different domains (e.g., Wigfield et al, 2016); however, their overconfidence does not guarantee high persistence on academic tasks nor high academic achievement (e.g., Zander et al, 2020). Moreover, even if expectations are low, children with high achievement task values for academic performance more readily persist in learning and achieve success when faced with challenging tasks (Chow et al, 2012; Guo et al, 2015; Wigfield & Gladstone, 2019).…”
Section: Relations Between Achievement Task Valuesmentioning
confidence: 99%
“…Though expectancy has been identified as a strong predictor of academic success in previous studies (see Wigfield & Eccles, 2020), it depends more on individuals’ confidence in their intellectual abilities and their experiences with the activities (Eccles, 2005). Due to cognitive immaturity, children are often overly optimistic about their competencies in different domains (e.g., Wigfield et al, 2016); however, their overconfidence does not guarantee high persistence on academic tasks nor high academic achievement (e.g., Zander et al, 2020). Moreover, even if expectations are low, children with high achievement task values for academic performance more readily persist in learning and achieve success when faced with challenging tasks (Chow et al, 2012; Guo et al, 2015; Wigfield & Gladstone, 2019).…”
Section: Relations Between Achievement Task Valuesmentioning
confidence: 99%
“…Participants in the study are 120 students selected from two schools in Addis Ababa, Ethiopia. Based on the findings from earlier studies, gender (Rodríguez et al, 2020;Zander et al, 2020), school type (Özgen and Bindak, 2011), and grade level (Wubalem, 2006;Özgen and Bindak, 2011) are important variables in students' mathematics self-efficacy. As such, an equal number of students from both genders, from both government and private high schools, and from both grades 9 and 10 (60 from each group) were included in the study.…”
Section: Sampling Technique and Sample Characteristicsmentioning
confidence: 99%
“…In practice, the effects of demographic variables on students' mathematics self-efficacy are still inconclusive. For instance, gender was found to be associated with students' mathematics self-efficacy, favoring males (Lloyd et al, 2005;Wu, 2016;Recber et al, 2018;Rodríguez et al, 2020;Zander et al, 2020). In a meta-analytic review of studies, males were found to have a higher MSE than their female counterparts (Huang, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Leyva, 2017). Mathematics self-efficacy beliefs, or beliefs in one's ability to do mathematics, have consistently been found to be lower in females than males, a worrying finding given that mathematics self-efficacy has also been shown to predict educational achievement and career outcomes (Zander et al, 2020). Zeldin et al (2008) show that different sources are predominant in the development of the self-efficacy beliefs of men and women in STEM careers.…”
Section: Personal Demographics That May Explain Variation In Efficacy...mentioning
confidence: 99%